Safe method for release of severe post burn neck contracture under tumescent local anaesthesia and ketamine - Agarwal, Pawan (Indian Journal of Plastic Surgery, 2004)
Severe post burn neck contracture results in difficult intubation, which can be life threatening and can result in multiple serious complications and sequels. Thirty patients with age ranging from 12 to 50 years were operated under local tumescent anesthesia supplemented with intravenous ketamine for release of post burn neck contracture and split skin grafted. This technique obviates the need for endotracheal intubation. There were no complications attributed to this anesthesia technique. There was no graft loss and blood loss was minimal.
Keywords: Neck contracture; Tumescent local anesthesia